2012
DOI: 10.1111/j.1365-277x.2012.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum retinol‐binding protein 4 concentrations and clinical indices in subjects with type 2 diabetes: a meta‐analysis

Abstract: The results obtained in the present study suggest that serum RBP4 concentrations in patients with type 2 diabetes may be associated with diabetes-related renal dysfunction and imbalances in lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…As an example, we confirm previously reported close relationships between circulating RBP4 and serum triglycerides [13], [14]. For RBP4, relationships with insulin resistance and glucose homeostasis have been controversially discussed [14], [15][17].…”
Section: Discussionsupporting
confidence: 90%
“…As an example, we confirm previously reported close relationships between circulating RBP4 and serum triglycerides [13], [14]. For RBP4, relationships with insulin resistance and glucose homeostasis have been controversially discussed [14], [15][17].…”
Section: Discussionsupporting
confidence: 90%
“…This may increase the risk of vitamin A deficiency in individuals who do not have adequate liver stores to draw from. In subjects with kidney disease, the glomerular filtration rate decreases, resulting in an increase in the serum concentration of apo-RBP (237) and a lower percentage of saturation with retinol than the typical 85%. This altered ratio would decrease the utility of RBP as a surrogate indicator of serum retinol concentration.…”
Section: Biomarker-specific Issuesmentioning
confidence: 99%
“…Other studies concluded that elevated RBP4 levels in patients with T2DM might be relevant to the development of insulin resistance state, owing to the potential mechanisms for RBP4 involved in insulin resistance . Besides renal function and insulin resistance, several studies have also revealed that circulating RBP4 had significantly positive correlations with the proatherogenic lipid parameters in T2DM patients , suggesting its possible role for lipid metabolic abnormalities in T2DM. However, the results of these studies regarding the major determinants of plasma RBP4 levels in T2DM patients were inconsistent and the underlying mechanisms were also inconclusive.…”
Section: Introductionmentioning
confidence: 99%